The hadeeth “Fasting in winter is a cold prize” Knowledge and Narration - Ahmed, Sabah Fathy Abdelrahman (Journal of Islamic Sciences, 2020)
The study addressed/ focused on just one speech of prophet’s speeches that repeats frequently on tongues, so it collected its methods, studied its origins, followed its narrators’ circumstances and investigated opinions of critics to judge on the methods and origins, then, the study presented /showed the summary of judgment on speech. The study has concluded that there are several methods’ origins can’t get rid of weak situation; also, some of them have very weak situations. It concluded that the speech is raised to the prophet, peace be upon him, by some of its methods, its pieces of evidence and diversity of its exits. Its board rises to the best for others, its verbal and syntaxes are valid and true. It is accepted and doable, but it’s forbidden to be one of the prophet’s speeches, peace be upon him, as a reservation, so it’s correct as a suspended one. The study reached to important results on the side of the novel represented in the issues learned from the speech of the study, the first benefit: fasting is a spiritual divine worship, the second benefit: the winter prize of the worshipers, The third benefit: Winter has a long night, for Prayers and recitation of worshipers, and recitation of the righteous. The fourth benefit: Worship, if accompanied by unintended hardship, is more rewarding.